Comparative Study Of The Incidence Of Family Entrepreneurship And Social Business Development In Two Areas Of La Libertad, 2022 - Aguilar Lujan, Mily Jovana (2024)
The objective of this study was to determine the incidence between family entrepreneurship and business social development in two areas of Libertad, 2022, for which I work with the applied method, quantitative approach, of a non-experimental design of a causal comparative level, where false As a population, 300 entrepreneurs from the footwear sector and 250 from Trujillo manufacturing, therefore, as a sample, there were 118 and 110 respectively for each business category, as a technique adapted the questionnaire for both cases. Results, with greater relevance in the family entrepreneurship variable, with 72% good in the footwear category and 62% regular manufacturing; Similarly, in the social aspect of development, 73% are good and 58% regular; respectively for each category. Therefore, it was concluded that the significant incidence with family entrepreneurship and business social development in the footwear and manufacturing areas of La Libertad will be determined, with (rho=0.810**) and (rho=0.759**) and p < 0.05. In this manner, the Ho is refuted and the Ha is admitted. For this reason, the relationship between the variables is evidenced, in addition, the linear regression, in both items it was obtained 75.20% and 53.70%, respectively, the rest is related to other factors.